PENGARUH LAYANAN SIRKULASI TERHADAP MINAT KUNJUNG PEMUSTAKA PADA DINAS PERPUSTAKAAN KOTA PONTIANAK - Pambudi, Fajar; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study discusses the effect of circulation services on the interest of visitors to visit the Pontianak City Library Service.The purpose of this study was to determine the circulation services that are applied in meeting the needs of visiting interest in the Pontianak City Library Service. It uses qualitative methods and the type of research used is field research or field study by collecting data through interviews, direct observation, and through documents. The number of informants in the study was 4 people. Determination of informants is based on the assessment of researchers on informants who are considered to control the data or object under study. The services owned by Pontianak City Library Service are quite interesting. Provision of services can be an added value to attract visitors to visit such as free wifi, bookshelves, reading tables, air conditioning, computers, OPAC (Online Public Access Catalog), and visitors feel interested in visiting the library because the collections available in the library are quite complete and fulfilling user information needs. Constraints experienced by visitors during a visit to the City Library are electricity cables that are still lacking, then the placement of manual paper that is felt to be out of place which makes visitors wonder, and storage of goods that are not safe because the cabinets are used using open cabinets.Â Keywords: Circulation Service, Library, Reader.